2016
DOI: 10.1016/j.jngse.2016.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of organic compounds from representative shales and the effect on porosity

Abstract: As the location and accessibility of hydrocarbons is key to understanding and improving the extractability of hydrocarbons in hydraulic fracturing, this study is an attempt to understand how native organics are distributed with respect to pore size to determine the relationship between hydrocarbon chemistry and pore structure in shales.First, selected shale cores from the Eagle Ford and Marcellus formations were subjected to pyrolysis gas chromatography (GC),thermogravimetric analysis, and organic solvent extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 53 publications
(85 reference statements)
3
21
0
Order By: Relevance
“…Previous studies generally found PSD curves of mudstone rise after solvent extraction, and the samples in their studies are dominantly lacustrine shale with moderate or relatively high TOC contents, and have high extract production [30,33,81]. Decreases of mesopore volumes or PSD curves of a few marine shales after solvent extraction have been reported [27,32,38]. While the PSD decreasing becomes more common for our samples.…”
Section: The Effects On the Mudstonessupporting
confidence: 49%
See 4 more Smart Citations
“…Previous studies generally found PSD curves of mudstone rise after solvent extraction, and the samples in their studies are dominantly lacustrine shale with moderate or relatively high TOC contents, and have high extract production [30,33,81]. Decreases of mesopore volumes or PSD curves of a few marine shales after solvent extraction have been reported [27,32,38]. While the PSD decreasing becomes more common for our samples.…”
Section: The Effects On the Mudstonessupporting
confidence: 49%
“…M-1, M-3 and M-4 are in this case. Solvent extraction inducing swelling of montmorillonite and illite/smectite has been observed [38,82]. The decrease of PSD of M-1, which is dominated by kaolinite (93.1 wt.…”
Section: The Effects On the Mudstonesmentioning
confidence: 98%
See 3 more Smart Citations